Optimization of annealing treatment and comprehensive properties of Cu-containing Ti6Al4V-xCu alloys. Issue 10 (October 2019) - Peng, Cong; Liu, Yang; Liu, Hui; Zhang, Shuyuan; Bai, Chunguang; Wan, Yizao; Ren, Ling; Yang, Ke
Abstract: The Ti6Al4V-Cu alloy was reported to show good antibacterial properties, which was promising to reduce the hazard of the bacterial infection problem. For the purpose of preparing Ti6Al4V-Cu alloy with satisfied comprehensive properties, it's important to study the heat treatment and the appropriate Cu content of the alloy. In this study, high Cu content Ti6Al4V- x Cu ( x  = 4.5, 6, 7.5 wt%) alloys were prepared, and firstly the annealing heat treatments were optimized in the α+β+Ti2 Cu triple phase region to obtain satisfied tensile mechanical properties. Then the effect of Cu content on the tribological property, corrosion resistance, antibacterial activity and cytotoxicity of the Ti6Al4V- x Cu alloys were systematically studied to obtain the appropriate Cu content. The results showed that the optimal annealing temperatures for Ti6Al4V- x Cu ( x  = 4.5, 6, 7.5 wt%) alloys were 720, 740 and 760 °C, respectively, which was resulted from the proper volume fractions of α, β and Ti2 Cu phases in the microstructure. The additions of 4.5 wt% and 6 wt% Cu into the medical Ti6Al4V alloy could enhance the wear resistance and corrosion resistance of the alloy, but the addition of 7.5 wt% Cu showed an opposite effect. With the increase of the Cu content, the antibacterial property was enhanced due to the increased volume fraction of Ti2 Cu phase in the microstructure, but when the Cu content was increased to 7.5 wt%, cytotoxicity was presented. A medium Cu content of 6 wt%, with annealing temperature of 740 °C make the alloy possesses the best comprehensive properties of tensile properties, wear resistance, corrosion resistance, antibacterial property and biocompatibility, which is promising for future medical applications.